Public Relations Management in Improving Umrah Pilgrims Services: A Case Study of Travel Wizarus - Torikoh Torikoh; Babun Suharto; Sri Rahayu; Christina Wulansari (CV. ULIL ALBAB CORP, 2024)
This study aims to investigate how public relations management can enhance Umrah pilgrim services. This research was conducted on Wizarus travel located in Tangerang, Banten Province. The method used in this study is qualitative with a descriptive approach. Data collection techniques use interviews, observations, and documentation. Data analysis is carried out in several steps, namely, data reduction, data presentation, and conclusion and verification. The results of this study show that: First, the public relations strategy carried out by travel Wizarus is carried out through education, multi-platform communication, and collaboration with influencers. Meanwhile, public relations management carried out by travel Wizarus is carried out in three forms, namely, analyzing the needs and expectations of Umrah pilgrims, improving service quality, and monitoring and evaluation. This study has limitations, namely it does not compare public relations management in other Umrah travel. Of course, each Umrah travel has different management according to the characteristics of Umrah travel. From the limitations in this study, the author recommends both researchers and academics, especially in the field of management studies, to continue research with the same theme, both the same and different research locus in the sense of a wider scope. This study aims to investigate how public relations management can enhance Umrah pilgrim services. This research was conducted on Wizarus travel located in Tangerang, Banten Province. The method used in this study is qualitative with a descriptive approach. Data collection techniques use interviews, observations, and documentation. Data analysis is carried out in several steps, namely, data reduction, data presentation, and conclusion and verification. The results of this study show that: First, the public relations strategy carried out by travel Wizarus is carried out through education, multi-platform communication, and collaboration with influencers. Meanwhile, public relations management carried out by travel Wizarus is carried out in three forms, namely, analyzing the needs and expectations of Umrah pilgrims, improving service quality, and monitoring and evaluation. This study has limitations, namely it does not compare public relations management in other Umrah travel. Of course, each Umrah travel has different management according to the characteristics of Umrah travel. From the limitations in this study, the author recommends both researchers and academics, especially in the field of management studies, to continue research with the same theme, both the same and different research locus in the sense of a wider scope.